The Role of Women Farming Families in Internalizing Economic Education Based on Local Wisdom - Restya Dwi Amalia; Cipto Wardoyo; Hari Wahyono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by the development of today's increasingly advanced technology that makes teenagers use money at will to buy goods online without thinking about their use so that women have such an important contribution to teaching economic education that has been taught from generation to generation. This research uses a qualitative approach to the type of phenomenology. The local people in this research are in Donowarih Village, KarangpIoso District, Malang Regency. The selection of informants carried out in the study was using the snowball technique. The data collection technique was carried out by interview, observation, and documentation. The results of the study show that women internalize economic education from an early age by applying things by using money with care, saving, and living frugally so that children become wise economic actors. Women internalize financial management by giving pocket money so that children can be responsible for the trust given. The perceived barriers include being lazy to help parents work, tending to behave conservatively, and having different opinions in terms of consumption patterns